Leveraging on social media as a communication channel for improving services of the government of Malaysia - Abdullah, Nur Farhana; Nadarajah, Devika; Raja Yusof, Raja Nerina; Abdul Latiff, Ahmad Shaharudin (Human Resource Management Academic Research Society, 2019)
In today’s competition, the private and public sector is taking social media to another level towards achieving their purposes, whether to improve profitability of the company or to improve organizational performance. Ubiquitous and innovative ICTs provide different communication channels for the public to give feedbacks on the services given the public sector. As such, social media provides an opportunity to gather feedbacks and responses towards improving services. The purpose of this paper is to give a background on leveraging social media to improve services in the Malaysian government sector. Based on the study background, observations and content analysis on the social media pages were carried out for the purpose of the study. It is understood that leveraging social media does have an advantage to give insights for successful social media implementation and can give a positive organizational effect to the departments.